Uncommon and peculiar soft tissue sarcomas: Multidisciplinary review and practical recommendations for diagnosis and treatment. Spanish group for Sarcoma research (GEIS – GROUP). Part I. (September 2021) - Martínez-Trufero, Javier; Cruz Jurado, Josefina; Gómez-Mateo, M.Carmen; Bernabeu, Daniel; Floría, Luis Javier; Lavernia, Javier; Sebio, Ana; García del Muro, Xavier; Álvarez, Rosa; Correa, Raquel; Hernández-León, C.Nieves; Marquina, Gloria; et al.
Graphical abstract: Highlights: General guidelines for sarcomas are of limited value or even not applicable for some uncommon sarcomas. Specific clinical and molecular characteristics of uncommon sarcoma subtypes imply specific diagnostic and therapeutic approaches. New multikinase inhibitors recently developed provide new therapeutic opportunities to some vascular and fibroblastic sarcomas. Patients suffering from these uncommon tumors deserve the same opportunities as other patients with more prevalent diseases, so specific clinical research in these subtypes should be promoted and supported.